2002
DOI: 10.1073/pnas.192582899
|View full text |Cite
|
Sign up to set email alerts
|

Chemical chaperones increase the cellular activity of N370S β-glucosidase: A therapeutic strategy for Gaucher disease

Abstract: Gaucher disease is a lysosomal storage disorder caused by deficient lysosomal ␤-glucosidase (␤-Glu) activity. A marked decrease in enzyme activity results in progressive accumulation of the substrate (glucosylceramide) in macrophages, leading to hepatosplenomegaly, anemia, skeletal lesions, and sometimes CNS involvement. Enzyme replacement therapy for Gaucher disease is costly and relatively ineffective for CNS involvement. Chemical chaperones have been shown to stabilize various proteins against misfolding, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
455
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(481 citation statements)
references
References 33 publications
(32 reference statements)
20
455
0
5
Order By: Relevance
“…While both treatments are effective in improving the hematologic and visceral symptoms in patients with mild, non-neuronopathic forms of the disease, their efficacy may be limited by their inability to cross the blood-brain barrier (ERT) or adverse side effects (SRT). Recent studies have demonstrated the ability of sugar analog inhibitors to increase the activity of mutant lysosomal enzymes in patient fibroblasts by acting as pharmacological chaperones [10][11][12][13][14][15]. As active site inhibitors, these compounds bind to the mutant enzymes and stabilize them in the ER, thereby preventing their ER-associated degradation and facilitating their folding and transport out of this compartment to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While both treatments are effective in improving the hematologic and visceral symptoms in patients with mild, non-neuronopathic forms of the disease, their efficacy may be limited by their inability to cross the blood-brain barrier (ERT) or adverse side effects (SRT). Recent studies have demonstrated the ability of sugar analog inhibitors to increase the activity of mutant lysosomal enzymes in patient fibroblasts by acting as pharmacological chaperones [10][11][12][13][14][15]. As active site inhibitors, these compounds bind to the mutant enzymes and stabilize them in the ER, thereby preventing their ER-associated degradation and facilitating their folding and transport out of this compartment to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Since fibroblasts derived from different N370S/N370S Gaucher patients can exhibit variable GlcCerase residual activity [2,10,15], we tested the ability of IFG to enhance enzyme activity from multiple N370S patient fibroblasts. The results are summarized in Table I.…”
Section: Ifg Enhances the Activity Of N370s Glccerasementioning
confidence: 99%
See 1 more Smart Citation
“…[7] Two GD patient fibroblast cell lines, one harboring N370S/N370S and the other F213I/L444P GCase mutations, were treated with IFG for five days and intracellular GCase activity following lysis of cells was determined with the aid of the artificial substrate 4-methylum-belliferylbeta-D-glucopyranoside (MUGlc). [30,31] An increase in enzymatic activity is observed as an increase in fluorescence upon release of the 4-methylumbelliferyl fluorophore. Treatment of N370S/N370S and F213I/L444P fibroblasts with 25 μM IFG for five days enhanced GCase activity 2.5-and 4.3-fold over non-pretreated cells, respectively (see Figure 1C).…”
Section: Ifg Enhances Global Stability and Activitymentioning
confidence: 99%
“…To this end, small molecular chaperones designed to cross the blood–brain barrier that are capable of increasing GCase activity are being investigated as a novel therapy for PD to decrease α‐synuclein levels 17, 18, 19, 20, 21, 22, 23, 24, 25…”
mentioning
confidence: 99%